Coix Seed Extract Prevents Inflammation-mediated Skin Dryness Induced by Sodium Dodecyl Sulfate Exposure in HR-1 Hairless Mice - Li, Feng; Nakanishi, Yusuke; Murata, Kenta; Shinguchi, Kanako; Fujita, Nina; Chiba, Shigeki; Takahashi, Ryuji (Planta Medica International Open, 2022)
Skin inflammation and dryness are the features of surfactant-induced irritant contact dermatitis, a common skin disorder. In Japan, Coix seed (CS, Coix lacryma-jobi L. var. ma-yuen Stapf) is widely used as a traditional medicine and functional supplement to treat skin inflammation and dry skin. However, the efficacy of CS against surfactant-induced skin disorders has not been reported. Here, we investigated the effect of CS on inflammatory dry skin disorders induced by multiple topical applications of sodium dodecyl sulfate (SDS), a representative anionic surfactant. Male HR-1 hairless mice received a water extract of CS for four weeks. Three weeks after CS administration, the dorsal skin of the mice was exposed once daily to 10% SDS for five days. CS efficacy was then evaluated by measuring epidermal water content; erythema index; severity of skin scaling; epidermal thickness; inflammatory cell infiltration; production of pro-inflammatory mediators, such as interleukin-1α (IL-1α) and prostaglandin E2 (PGE2); and protein expression of cyclooxygenase 2 (COX-2), in the dorsal skin. Administration of CS markedly attenuated the SDS-induced reduction in epidermal water content, elevated erythema index, and severity of skin scaling. Histological analysis demonstrated that CS suppressed epidermal hyperplasia and macrophage infiltration in SDS-exposed skin. Furthermore, CS significantly prevented SDS-induced production of IL-1α and PGE2, as well as COX-2 upregulation. These results indicate that CS prevents SDS-induced inflammation-mediated skin dryness by inhibiting the production of pro-inflammatory mediators.
Keywords: Coix lacryma-jobi L. var. ma-yuen Stapf; Gramineae; Coix seed; Sodium Dodecyl Sulfate; Skin inflammation; Skin dryness